Determinan Kualitas Layanan Akademik Di STMIK Mardira Indonesia Bandung - Ali Mulyawan; Iwan Sidharta (Jurnal Computech & Bisnis (e-Journal), 2014)
The quality of academic services provided by the university is one of the important factors related to the credibility of college. Previous studies mentioned that the quality of education services is closely related to student satisfaction. It is thus necessary for the determination of the quality factor of academic services provided to students in order to improve the quality of higher education. This study was conducted to determine the determinant factors related to the quality of academic services by using exploratory method with stratifield random sampling of 83 students based on a calculation formula slovin alpha level of 10%. The results showed that the most influential factor on the quality of academic services is responsiveness whereas the lowest effect is influenced by physical evidence. Keywords: quality of service; services; college